Development of structural schemes for collecting monitoring and diagnostic data of signaling points of the railway run based on programmable logic controllers - Qurbonali Nuriddinov Komiljon o’g’li; Asadulla Azizov Raximovich (Journal of Artificial Intelligence and Digital Economy, 2024)
The article talks about the problems and shortcomings of collecting various diagnostic data at signal points of existing dispatching control systems of railway automation. As a solution to these problems, structural schemes for collecting analog and discrete diagnostic data have been developed based on a programmable logic controller. On the basis of the developed structural schemes, tests were conducted on measuring voltages in two types of analog signals, and the results of the dependence of the mean square deviation on the request time in determining the effective value of the voltage were given